2012
DOI: 10.1117/1.jrs.6.063594
|View full text |Cite
|
Sign up to set email alerts
|

Absolute radiometric calibration of the KOMPSAT-2 multispectral camera using a reflectance-based method and empirical comparison with IKONOS and QuickBird images

Abstract: This paper presents absolute radiometric calibration coefficients (gains) that explain the relationship between the digital number (DN) and at-sensor radiance for the multispectral camera (MSC) on Korea's first high-resolution satellite (KOMPSAT-2). Absolute radiometric calibration was performed using a reflectance-based method. In addition, the suitability of vicarious results from radiance-and reflectance-based validations was analyzed with reference to IKONOS and QuickBird images. The latter are spectrally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…After launch, in-flight calibration was performed by the onboard calibrator every 33 days (originally 17 days; currently 49 days) [11]. The vicarious calibration based on a reflectance-based approach [12][13][14][15][16] has been conducted jointly by Saga University, the University of Arizona and the National Institute of Advanced Industrial Science and Technology, Japan (AIST), over dry lakes in Nevada, U.S.A., such as Railroad Valley Playa and Ivanpah Playa [17]. The cross-calibration with the Moderate Resolution Imaging Spectroradiometer (MODIS) onboard Terra was performed over the vicarious calibration sites [18].…”
Section: Introductionmentioning
confidence: 99%
“…After launch, in-flight calibration was performed by the onboard calibrator every 33 days (originally 17 days; currently 49 days) [11]. The vicarious calibration based on a reflectance-based approach [12][13][14][15][16] has been conducted jointly by Saga University, the University of Arizona and the National Institute of Advanced Industrial Science and Technology, Japan (AIST), over dry lakes in Nevada, U.S.A., such as Railroad Valley Playa and Ivanpah Playa [17]. The cross-calibration with the Moderate Resolution Imaging Spectroradiometer (MODIS) onboard Terra was performed over the vicarious calibration sites [18].…”
Section: Introductionmentioning
confidence: 99%
“…For the Gaofen-1 satellite data, no definite coefficient for TCT has yet to be developed; however, by comparing the parameters of the WFV cameras sensor of Gaofen-1 with known satellite sensors with Tasseled Cap transform coefficients, it was found that the WFV sensor and the IKONOS satellite sensor have a similar number of bands and spectral range of bands [59]. As the TCT conversion coefficient is fixed and determined by the band number and band range of a sensor, the conversion coefficient of the IKONOS satellite was selected in this paper (Table 1) [60,61].…”
Section: Datamentioning
confidence: 99%
“…After launching the KOMPSAT series, radiometric calibration and validation was applied to the imagery by the Korean Aerospace Research Institute (KARI) and Pukyong National University (PKNU) [10,11]. This paper examines the laboratory-based prelaunch calibration conducted by KARI, together with the post-launch absolute calibration and cross calibration executed by a tag team of KARI and PKNU scientists during the LEOP.…”
Section: Introductionmentioning
confidence: 99%